Tinjauan Fikih Muamalah Terhadap Praktik Jual Beli Rumput Laut di Desa Lontar - Hayati, Ela; Khadafi, Muammar; Muhammad, Iqbal Fadli (Department of Islamic Economics Law, 2024)
This research aims to find out and review how muamalah jurisprudence applies to the practice of buying and selling seaweed in Lontar Village, Tirtayasa District, Serang Regency. The type of research carried out by the author is field research and uses a qualitative approach, while the data collection techniques used are interviews, observation and documentation. The research results show that the contract used in buying and selling seaweed in Lontar Village is included in the Salam contract. In terms of harmony and conditions, it is in accordance with the form of buying and selling greetings. After analyzing from the perspective of the Muamalah Fiqh Review, the practice of buying and selling seaweed in Lontar village does not meet the terms and conditions of the salam contract, due to the inconsistency of the goods and delays in the time when the goods are given, this is caused by technical factors (weather) that cannot be predicted, So there is no element of intent in it, and both parties are mutually happy in responding to this problem, so that buying and selling seaweed in the Lontar village is legal. Because buying and selling is valid when both parties are mutually happy and willing